2011
DOI: 10.1021/ja202739j
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral Atom Ordering in a Zeolite Framework: A Key Factor Affecting Its Physicochemical Properties

Abstract: Table S2. Data Collection and Crystallographic Parameters for the Hydrated and Dehydrated Forms of K +-Exchanged Gallosilicate Natrolites with Different Degrees of T-atom Ordering material K-GaNAT-I(E) K-GaNAT-II(E) K-GaNAT-III(E) K-GaNAT-I(EC) K-GaNAT-II(EC) K-GaNAT-III(EC) unit cell composition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 37 publications
5
38
0
Order By: Relevance
“…This strongly suggests that both j and q are almost independent of the T-atom ordering, but is highly dependent on the type of extraframework cations, which is consistent with the trend found in the Na þ form of natural aluminosilicate and synthetic gallosilicate natrolites [23,30]. Fig.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…This strongly suggests that both j and q are almost independent of the T-atom ordering, but is highly dependent on the type of extraframework cations, which is consistent with the trend found in the Na þ form of natural aluminosilicate and synthetic gallosilicate natrolites [23,30]. Fig.…”
Section: Resultssupporting
confidence: 84%
“…A similar result has also been observed for the dehydrated K þ form of the natural mineral natrolite, whereas a much longer time (7 days) was necessary to achieve rehydration when exposed to ambient conditions [34]. This behavior is substantially different from their gallosilicate analogs (i.e., K-TNU-3 and K-TNU-4), which show irreversible hydration after calcination [30]. When the Na þ back-exchange is performed on calcined K-PST-3 and K-PST-4, both materials attained almost complete Na þ backexchange, unlike the case of calcined K-TNU-3 and K-TNU-4 that show a strong dependency on T-atom ordering [30].…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Very recently, it has been shown that the cation exchange ability of gallosilicate natrolites is strongly dependent on Si, Ga ordering, and that this is very likely related to a more fl exible framework in the more disordered natrolites. [ 36 ] In these cation exchange studies, but also in the one commented above on the selective adsorption properties of PST-1, [ 35 ] the crystallographic sizes of the windows are so small that any traffi c along the pores of the chemical species involved in the processes (either cations or small molecules) requires a large degree of framework deformation that can open the pores.…”
Section: Research Newsmentioning
confidence: 99%